-6+6x+7=(x+1)-2

Simple and best practice solution for -6+6x+7=(x+1)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+6x+7=(x+1)-2 equation:


Simplifying
-6 + 6x + 7 = (x + 1) + -2

Reorder the terms:
-6 + 7 + 6x = (x + 1) + -2

Combine like terms: -6 + 7 = 1
1 + 6x = (x + 1) + -2

Reorder the terms:
1 + 6x = (1 + x) + -2

Remove parenthesis around (1 + x)
1 + 6x = 1 + x + -2

Reorder the terms:
1 + 6x = 1 + -2 + x

Combine like terms: 1 + -2 = -1
1 + 6x = -1 + x

Solving
1 + 6x = -1 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
1 + 6x + -1x = -1 + x + -1x

Combine like terms: 6x + -1x = 5x
1 + 5x = -1 + x + -1x

Combine like terms: x + -1x = 0
1 + 5x = -1 + 0
1 + 5x = -1

Add '-1' to each side of the equation.
1 + -1 + 5x = -1 + -1

Combine like terms: 1 + -1 = 0
0 + 5x = -1 + -1
5x = -1 + -1

Combine like terms: -1 + -1 = -2
5x = -2

Divide each side by '5'.
x = -0.4

Simplifying
x = -0.4

See similar equations:

| -40-8=6s | | -2=0-1/5j | | 9-5a+a=-3 | | 6n-7(n-1)=12 | | 2m+6=2m-2 | | 5(z+6)=2+3z | | (6/5(p-4))-(6/5p) | | 0=16t^2+138t+55 | | 6a+2a+12=7+6a+3 | | 4x-5+2x=13 | | y=4x^2-6x-7 | | 0=16t^2+138t+c | | x^2-y^2=50 | | x+8+5x=2-2x | | 2x^3+7x^2-15=0 | | 7.6x-1.6=13.6 | | 2k=56 | | m-7m+6=20 | | -5k+3=-6+4k | | 6(k-3)-7=6k-(5k-2) | | x^2-x^2-2+1=7 | | 55r^2+28r-3= | | -y-2=11 | | 2(7x+3)+4=7(2x-1)+2x | | 7y/12-5=9-4y/3 | | 8+4=2(x-12) | | -70-2.25x=182.50 | | 2138=n+38 | | 10x+20xy+7y=100 | | 3x-7=2(x-4)+15 | | 7u-5u=-43 | | y-12=70 |

Equations solver categories